Discovery of antiproliferative and anti-FAK inhibitory activity of 1, 2, 4-triazole derivatives containing acetamido carboxylic acid skeleton. (15th May 2021) - Mustafa, Muhamad; Abuo-Rahma, Gamal El-Din A.; Abd El-Hafeez, Amer Ali; Ahmed, Esam R.; Abdelhamid, Dalia; Ghosh, Pradipta; Hayallah, Alaa M.
Graphical abstract: Highlights: A series of 1, 2, 4-triazoles were designed and synthesized as potent FAK kinase inhibitors. The In vitro antiproliferative activity was evaluated against HepG2 and Hep3B cell lines. Compounds 3c and 3d showed the highest promising anticancer activities. Western blot analysis showed that both 3c and 3d repressed FAK phosphorylation significantly. Molecular modeling was carried out in the ATP binding site of FAK. Abstract: Small molecule inhibitors of the focal adhesion kinase are regarded as promising tools in our armamentarium for treating cancer. Here, we identified four 1, 2, 4-triazole derivatives that inhibit FAK kinase significantly and evaluated their therapeutic potential. Most tested compounds revealed potent antiproliferative activity in HepG2 and Hep3B liver cancer cells, in which 3c and 3d were the most potent (IC50 range; 2.88 ~ 4.83 µM). Compound 3d possessed significant FAK inhibitory activity with IC50 value of 18.10 nM better than the reference GSK-2256098 (IC50  = 22.14 nM). The preliminary mechanism investigation by Western blot analysis showed that both 3c and 3d repressed FAK phosphorylation comparable to GSK-2256098 in HepG2 cells. As a result of FAK inhibition, 3c and 3d inhibited the pro-survival pathways by decreasing the phosphorylation levels of PI3K, Akt, JNK, and STAT3 proteins. This effect led to apoptosis induction and cell cycle arrest. Taken together, these results indicate that 3d could serve as a potent preclinical candidate for the treatment of cancers.